Art nature dialogues : interviews with environmental artists - Grande, John K. (State University of New York Press, 2004)
"Art Nature Dialogues offers interviews with artists working with, in, and around nature and the environment. The interviews explore art practices, ecological issues, and values as they pertain to the siting of works, the use of materials, and the ethics of artmaking. John K. Grande includes interviews with Hamish Fulton, David Nash, Bob Verschueren, herman de vries, Alan Sonfist, Nils-Udo, Michael Singer, Patrick Dougherty, Ursula von Rydingsvard, and others."--Jacket